NOVEL NESPRIN-1 MUTATIONS DISRUPT NE ORGANIZATION AND INDUCE DILATED CARDIOMYOPATHY. (21st November 2014) - Zhou, C; Li, C; Zhou, B; Rao, L; McNally, EM; Shanahan, CM; Zhang, QP
Abstract : Nesprins comprise a family of multi-isomeric scaffolding proteins that bind to lamin A/C, emerin and SUN1/2 at the nuclear envelope (NE) to form the linker of nucleoskeleton and cytoskeleton (LINC) complex. Mutations in nesprin-1 and -2 contribute to Emery–Dreifuss muscular dystrophy and dilated cardiomyopathy (DCM). Following mutation screening in Syne-1 and -2 genes in 218 DCM patients and 210 healthy controls, we identified 7 patients harbouring three novel nesprin-1 mutations (R434Q, S566C, N591K) in the C-terminus of nesprin-1α, an evolutionarily conserved region containing the lamin and emerin binding domains. To explore roles of nesprin-1 in the pathogenesis of DCM, overexpression of GFP-tagged wildtype and nesprin-1α mutant constructs was performed. Nesprin-1α localised to the NE in all transfected cells, however, cells transfected with the S566C construct showed significantly increased numbers of convoluted nuc lei. Immunofluorescence demonstrated lamin A/C was mislocalised by the S566C mutant construct and SUN2 was mislocalised by all mutants. GST pull-down showed all nesprin-1 mutants had significantly reduced binding affinity to lamin A. Furthermore, GFP tagged nesprin-1 KASH and three mutants dramatically increased the amount of pERK compared with GFP alone and nesprin-1 WT in transfected myoblasts. In addition, WB showed significant up-regulation of ERK activity in both EDMD-DCM patient cells and nesprin-1 KASH knockout mice hearts, suggesting that nesprin-1 mutations can deregulate ERK signalling in the heart. These data suggest the nesprin mutants disrupt the LINC, uncoupling the NE from the cytoskeleton and leading to aberrant activation of mechanotransduction signalling; processes that may underlie the mechanism of cardiomyopathy.